Gene-Specific Targeting of DNA Methylation in the Mammalian Genome - Urbano, Arthur (Cancers (Basel), 2019)
DNA methylation is the most widely-studied epigenetic modification, playing a critical role in the regulation of gene expression. Dysregulation of DNA methylation is implicated in the pathogenesis of numerous diseases. For example, aberrant DNA methylation in promoter regions of tumor-suppressor genes has been strongly associated with the development and progression of many different tumors. Accordingly, technologies designed to manipulate DNA methylation at specific genomic loci are very important, especially in the context of cancer therapy. Traditionally, epigenomic editing technologies have centered around zinc finger proteins (ZFP)- and transcription activator-like effector protein (TALE)-based targeting. More recently, however, the emergence of clustered regulatory interspaced short palindromic repeats (CRISPR)-deactivated Cas9 (dCas9)-based editing systems have shown to be a more specific and efficient method for the targeted manipulation of DNA methylation. Here, we describe the regulation of the DNA methylome, its significance in cancer and the current state of locus-specific editing technologies for altering DNA methylation.